Ukrainian liberation movement of the 1940s-1950s: The institutionalization of researches (selected aspects) (continuation) - Ukhach, Vasyl (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The institutionalization processes of research of the Ukrainian liberation movement subjects in the period of 1940-1950-s are analyzed in the context of the state policy of commemoration. Many measures were provided in order to legally regulate their fight against totalitarian regimes. It is established that during the period from 1991 to 2004 there were careful attempts to study and evaluate the activities of the OUN and of the UPA. The OUN and the UPA problems contained a set of socio-political, ideological and value elements. On December 6, 2018, the Verkhovna Rada of Ukraine amended the law, giving the UPA soldiers the status of combat veterans and providing them with social protection. Non-governmental, scientific and public institutions played a significant role in the development and popularization of the Ukrainian liberation movement, particularly, very important work was done by the Centre of liberation movement researches. The Centre provided not only the researches, but also conducted educational campaign in order to objectively highlight the national liberation struggle of Ukrainians for freedom and independence during the first half of the XX century.